Does Military Expenditure Hinder Economic Growth? Evidence from Major Countries of the World - Bishnoi, C.R.; Vashistha, Ayushi; Shekhawat , Sonal (Thailand and The World Economy, 2025)
This study endeavours to investigate the effect of military expenditure on economic growth in ten major countries of the world, which collectively contributed 75.2 per cent to global military expenditure in 2022. The period of study is 30 years, from 1992 to 2022, determined solely based on the availability of data. The selected major countries are the USA, China, Russia, India, Saudi Arabia, the UK, Germany, France, South Korea, and Japan. Employing a panel data model, this study estimated the Pooled Ordinary Least Squares Model, Fixed Effects Model (FEM) and Random Effects Model. After model estimation, model selection tests were applied, and it was found that the FEM is the appropriate one. However, when diagnostic tests were applied to the FEM, it revealed that the FEM suffers from the issues of cross-section dependence, heteroskedasticity and endogeneity. Therefore, FGLS, first difference GMM, and system GMM were used for the robustness, and the results identify military expenditure and gross capital formation as the most significant factors influencing economic growth. Military expenditure shows a negative effect, while gross capital formation shows a positive effect on economic growth. The reliability of the GMM estimators is confirmed by the Sargan and Hansen J-tests, indicating that the instruments used are valid. Additionally, the absence of second-order autocorrelation further supports the robustness of the GMM results. These findings offer a nuanced understanding of the underlying dynamics and suggest that countries worldwide should adopt peacekeeping policies, curtail military expenditures, and allocate scarce resources used in military operations to alternative sectors, which can ensure high economic growth worldwide.